PERKEMBANGAN WATAK TOKOH UTAMA DALAM NOVEL GELOMBANG KARYA DEWI LESTARI - Melani, Aulia; Martono, Martono; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the researchers' interest in the character and development of character in the main characters of the novel Gelombang. The purpose of this research is to describe the development of the character of the main character in the novel Gelombang by Dewi Lestari. This study uses a descriptive method, in the form of qualitative, with a literary psychology approach. Based on data analysis, the main character has positive and negative characters. Positive characteristics include smart, diligent reading, clever foreign language, ambitious, hardworking, honest, and detailed. Negative characteristics include cowardice, fear of sleep, resignation, panic, surprise, and confusion. The character development of the main characters includes: normal being afraid of sleep; clever to be multilingual; dare to take action; and fear of sleeping to be brave to face sleep. Alfa figures are dynamic figures. This novel is very appropriate to be used as material for learning Indonesian language and literature because the contents of this novel can train students to understand the intrinsic elements presented by the author in his work. Keywords: Character Development, Novel.